2021
DOI: 10.3390/app112412070
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Application of Tuned Mass Dampers for Chatter in Turning of a Thin-Walled Cylinder

Abstract: Chatter is more likely to occur during the turning process of a thin-walled cylindrical workpiece owing to the low rigidity of such workpieces. Chatter causes intensive vibration, deterioration of the surface finish accuracy, tool damage, and tool wear. Tuned mass dampers (TMD) are usually applied as a passive damping technique to induce a large damping effect using a small mass. This study experimentally investigated the effect of the mounting arrangement and tuning parameters of the TMDs on the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, in [26], a cutteroscillator with a flexible holder in the X-axis direction was used to study the effect of changing the cutting speed on the suppression of regenerative chatter. In the study [15], the influence of the scheme of attaching dampers with tuned mass on the occurrence of vibrations in the process of turning a thin-walled cylinder, which in turn was an oscillator, was determined. In [27], a special design of an oscillator of low stiffness along the X-axis was used to study vibration in the turning process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in [26], a cutteroscillator with a flexible holder in the X-axis direction was used to study the effect of changing the cutting speed on the suppression of regenerative chatter. In the study [15], the influence of the scheme of attaching dampers with tuned mass on the occurrence of vibrations in the process of turning a thin-walled cylinder, which in turn was an oscillator, was determined. In [27], a special design of an oscillator of low stiffness along the X-axis was used to study vibration in the turning process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theoretical analysis and experimental verification have demonstrated that the application of TMDs in reducing chatter during the turning of the thin-walled cylinder also shows a good control performance [15]. Vibration control analyses of a high-rise structure indicate the effectiveness of linearizing the equations of motion to obtain optimal control device parameters [16]. Moreover, the pendulum TMDs installed at the top of Shanghai Tower and Taipei 101 significantly mitigate the wind-induced vibrations, thereby improving the comfort levels of residents [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when the dynamic vibration absorber deviates from the ideal design state due to changes in the damping ratio or natural frequency of the main vibration system, the performance of vibration control also declines. Therefore, multiple dynamic vibration absorbers [4][5][6][7][8] were developed, for which two or more dynamic vibration absorbers are utilized in parallel on the main vibration structure, to improve the robustness of dynamic vibration absorbers and accomplish multi-modal vibration suppression. Despite a slight increase in the dynamic vibration absorber's vibration suppression frequency band due to this method, the band is still not particularly wide.…”
Section: Introductionmentioning
confidence: 99%